BACHELOR OF SCIENCE IN INDUSTRIAL ENGINEERING PROGRAM AT CEBU TECHNOLOGICAL UNIVERSITY – DANAO CITY CAMPUS: PROPOSALS - Castilla, Delfa G. (Journal of Agriculture and Technology Management, 2012)
This study assessed the implementation of Bachelor of Science in Industrial Engineering (BSIE) at Cebu Technological University – Danao City Campus from the year 2004-2009 with the end view of formulating proposals for the improvement of the aforementioned curriculum based on the findings on the analysis done on the profile of the respondents and status of BSIE Program instruction using the questionnaire as the main tool in gathering data. The implementation of the BSIE Program had the folllowing findings: There were 11 instructors who had not finished Master’s Degree; three (3) instructors need retraining in the subjects like CADD/CAM, Management Information System, Systems Engineering and Facilities Planning and Design; Majority of the instructors did not have the work experience in the industry; There were more female than male and they were at the right age in each year level; Female were doing good in their studies compared to male; Majority claimed that it was their own decision in taking up the course; Most of their family belonged to the poverty threshold; Instructors claimed that the BSIE Program Objectives had been fully attained but the students perceived that these were partially attained; Both respondent’s group perceived that instructional materials were visible and ready for use sometimes; Lecture method of instruction was always used by the instructors; The students perceived that the instructors had partially delivered the instruction and they had also partially acquired it; The topmost problem was “shop not a replica of the industry” with the topmost solution as “acquiring more equipment / machines through budgetary proposals”. It is recommended that the Action Plan to improve the Implementation of BSIE Program be adopted.